Caracterización de la Planta Turística, oferta alimentación del cantón Sigchos. - Changalombo Valencia, Carlos Alberto (2020)
Food establishments at national at global level are one of the most representative components and services offeteing the plant ,and therefore of a place, for this reason is the main problem of food supply service at Sigchos canton during the last years It has been the lack of registration of different establishments currently existing there, since most of them are not found in any cantonal cadastre, that is why through different processes and research methods it was possible to cover this problem ; For this, a situational diagnosis of the canton in question was carried out, through a research in primary and secondary forts where it was possible to compile and form a baseline with economic, social, environmental and tourist information aspects; Consequently, an inventory food services was carried out the application the form for inventory of tourist plant food and beverages of MINTUR technical sheets, inventory card which served to characterize existing establishments; 43 places were inventories the among the categories the restaurant, bar and cafeteria; From this, an analysis was made taking into account certain parameters such as: good practices and food handling, service and infrastructure, resulting in only 15 establishments net had the minimum technical standards for operation were taken,inte account and are the ones that are listed in the catalog; There is information such as the owner's name; address, name, and category of the establishment, there is also a referential photograph, services and infrastructure. It is in this way that the entire research project will contribute to the promotion and development of tourism in the canton by having a catalog that will help tourists to choose one or another establishment according to their choice.